ANALISIS USAHA DAN STRATEGI PEMASARAN PADA PENANGKARAN IKAN ARWANA DI PT SUMATERA AQUAPRIMA BUANA KELURAHAN MUARA FAJAR KECAMATAN RUMBAI KOTA PEKANBARU - Cepriadi '; Eri Sayamar; Candra Irawan (Fakultas Pertanian, Universitas Riau, 2010)
Arwana fish (Scleropages formosus) is categorized as protected wild animal. This fish hasexclusive and beautiful appearance and it is used as prestigious symbol, pride and lucky charm.This research was conducted at PT. Sumatera Aquaprima Buana in Muara Fajar, Rumbai,Pekanbaru, from October until December 2008. The result showed that the production ofArwana fish in 1 period (3 months) produced 1.927 fish with various selling prince with theearning of Rp. 732.260.000, and the net earning was Rp. 420.171.683,33 by RCR 2,35. It isefficient because the RCR is more than 1 so this business is a prospective one. SWOT Analysisresulted in three priorities: 1) Minimize net-operating cost for fish meal by producing own fishmeal, 2) Expand the market share by expanding marketing network. 3) Join exhibition tostimulate local or domestic consumers.